Role of yoga in improving pulmonary efficiency in post-menopausal women - Bhaskar, Aniket; Kumar, Brajesh; Bhat, Ramesh M.; Kabir, Anwarul (International Journal of Research in Medical Sciences, 2023)
Background: Menopause is a natural transition in a women’s life. Menopausal transition has been linked to impairment of respiratory function. Female hormones play an important role in overall lung health. Yoga is an ancient Indian science as well as the way of life, which includes practice of yogasana in specific posture and pranayama which includes the regulated breathing techniques. The aim of the study was to evaluate the cumulative effect of practicing yoga and pranayamas on certain respiratory parameters and physical characteristics in post-menopausal women. Methods: A total of forty post-menopausal women (46-60 years) were divided into two groups. Group I was control group (women not doing yoga) and group II was regularly doing yoga for one year. Based on the duration of yoga- pranayama and meditation, the respiratory parameters such as VC, FVC, FEV1, PEFR, and FEF50 was measured with the help of vitalograph (pneumotrac; 11). Data collected were compiled, categorized and statistically analyzed, t-test was used for comparing the effect of yoga between the two groups and p≤0.05 was considered as statistically significant. Results: One-year yoga showed a significant decrement in Body weight (p<0.001) and Body Mass Index (p<0.01). Group II showed significant improvement (p<0.001) in all the respiratory parameters such as VC, FVC, FEV1, PEFR, and FEF50 when compared to respective control group. Respiratory rate was decreased significantly (p<0.0001) and Breath hold time was increased significantly (p<0.0001) when compared to control group. Conclusions: The present study demonstrated that the one-year of yogic practice is suitable for improving pulmonary efficiency and physical characteristics in post-menopausal women.